Nutritional status and depression among young adults treated in an outpatient consultation service at a national hospital in Junín, Peru, 2023 - Lara Romero, Yuliza Beronica (2024)
Objective: To assess the association between nutritional status and depression among young adults treated in an outpatient consultation service at a national hospital in Junín in 2023. Materials and methods: This quantitative, cross-sectional study was conducted with 346 young adults treated at Hospital Regional Docente Clínico Quirúrgico Daniel Alcides Carrión in Junín, Peru. Depression levels were assessed using the Beck Depression Inventory, while nutritional status was determined through anthropometric measurements such as weight, height, waist circumference (WC) and neck circumference (NC). The statistical analysis was performed using the Kolmogorov-Smirnov normality test, followed by the nonparametric chi-square test with IBM SPSS Statistics 27.0. The study received approval from the Hospital’s Ethics Committee. Results: A total of 54.91 % of the participants were female, and the predominant age group was 18 to 24 years. Moderate to severe depression was observed in 27.46 % of the participants and over 50 % showed some degree of depression. Additionally, 25.72 % were overweight, 4.05 % were obese, 17.34 % were at high risk for central obesity, and 22.83 % were at high cardiometabolic risk. However, when assessing the association between the indicators of nutritional status and depression, no statistically significant relationships were found, evidenced by a p value of 0.283 for body mass index, 0.095 for WC and 0.069 for NC. Conclusions: In the young adults from the studied sample, no association was found between the nutritional status of those with central obesity and cardiometabolic risk and their depression levels.